2021
DOI: 10.1038/s41420-020-00398-5
|View full text |Cite
|
Sign up to set email alerts
|

ADO/hypotaurine: a novel metabolic pathway contributing to glioblastoma development

Abstract: Significant advance has been made towards understanding glioblastoma metabolism through global metabolomic profiling. However, hitherto little is known about the role by which altered metabolism plays in driving the aggressive glioma phenotype. We have previously identified hypotaurine as one of the top-ranked metabolites for differentiating low- and high-grade tumors, and that there is also a strong association between the levels of intratumoral hypotaurine and expression of its biosynthetic enzyme, cysteamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…A recent study was reported in which ADO was abrogated using CRISPR/Cas9-mediated gene editing. This limited the proliferation of glioblastoma cells in vitro and tumor growth in vivo in a mouse model [96]. These findings strongly support the role of hypotaurine as an oncometabolite in glioblastoma and point to potential druggable targets for this tumor.…”
Section: Hypotaurinesupporting
confidence: 61%
“…A recent study was reported in which ADO was abrogated using CRISPR/Cas9-mediated gene editing. This limited the proliferation of glioblastoma cells in vitro and tumor growth in vivo in a mouse model [96]. These findings strongly support the role of hypotaurine as an oncometabolite in glioblastoma and point to potential druggable targets for this tumor.…”
Section: Hypotaurinesupporting
confidence: 61%
“…For example, 5-methylthioadenosine (MTA), a sulfur-containing nucleoside has recently reported as tumor suppresser 47 . Another cancer associated compound, hypotaurine, a sulfinic acid with antioxidant properties, derived from cysteine and an intermediate in taurine production, is one of the top ranked metabolites for differentiating low and high grade tumors 48 but was also shown to evoke a malignant phenotype in glioma, the most common primary brain malignancies in adults 49 . It is also marketed as a dietary supplement, together with taurine and L-carnitine and associated with semen quality improvement 50 .…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 25, 2022. ; https://doi.org/10.1101/2022.01.24.477528 doi: bioRxiv preprint ranked metabolites for differentiating low and high grade tumors 48 but was also shown to evoke a malignant phenotype in glioma, the most common primary brain malignancies in adults 49 . It is also marketed as a dietary supplement, together with taurine and L-carnitine and associated with semen quality improvement 50 .…”
Section: Experimental Confirmation Of Genomics Contribution To Food Knowledgementioning
confidence: 99%
“…Taurine is an amino sulfonic acid not used for protein synthesis, but with several physiological roles as osmotic pressure controller, neuromodulator and immunomodulator ( Shen et al, 2021 ). Taurine is synthesised either from cysteine oxidation via cysteine dioxygenase, which generates cysteinesulfinate that is decarboxylated by cysteinesulfinic acid decarboxylase, or from cysteamine oxidation by cysteamine (2-aminoethanethiol) dioxygenase (ADO) ( Ueki and Stipanuk, 2009 ).…”
Section: Glioblastomamentioning
confidence: 99%
“…ADO expression is significantly higher in GBM when compared to lower grade gliomas and its expression is upregulated in GSCs. Moreover, ADO overexpression promotes glioma stemness via NF-κB signalling ( Shen et al, 2021 ).…”
Section: Glioblastomamentioning
confidence: 99%